PENGARUH PENGALAMAN PENGENALAN LAPANGAN PERSEKOLAHAN (PLP) TERHADAP KESIAPAN KARIR PADA MAHASISWA PENDIDIKAN OLAHRAGA DAN KESEHATAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JAMBI - Ikhwan Hakim; Reza Hadinata; Sugih Suhartini (JURNAL ILMU KEOLAHRAGAAN, 2026)
Career readiness is an important aspect for education students in facing the transition from higher education to the professional workforce. Increasingly competitive job markets and the demands of teacher professionalism require students not only to master theoretical knowledge but also to possess relevant practical experience and mental readiness to carry out their roles as educators. One of the efforts made by universities to prepare students’ careers is through the School Field Introduction Program (Pengenalan Lapangan Persekolahan / PLP), which is designed to provide students with real experiences in the school environment. However, based on preliminary findings in the field, the career readiness of students in the Physical Education and Health Education program still shows variation and tends to be suboptimal. This study aims to analyze the effect of the School Field Introduction Program (PLP) experience on career readiness among students of the Physical Education and Health Education Study Program, Faculty of Teacher Training and Education, Universitas Jambi. This research employed a quantitative approach using an ex post facto method. The research population consisted of Physical Education and Health Education students who had participated in the PLP program, with the sample determined according to the characteristics of the research population. Data were collected using a career readiness questionnaire that had been tested for validity and reliability, and were analyzed using simple linear regression. The results of the study indicate that there is no positive and significant effect of the School Field Introduction Program (PLP) on students’ career readiness. The statistical test results show that the calculated t-value of −1.025 is smaller than the t-table value of 1.666, thus the alternative hypothesis (Ha) is rejected and the null hypothesis (Ho) is accepted. These findings indicate that the PLP experience does not have a significant effect on career readiness to become a teacher among Physical Education and Health Education students. This suggests that students’ career readiness is not solely determined by PLP experience, but is also influenced by other factors such as individual motivation, interest in the teaching profession, and self-development experiences outside the PLP program, including organizational involvement and other related activities